A Study on Assessment of Severity of Anaemia Among Urban and Rural Children of Belagavi, Karnataka - Abhishek Prayag; Girija S Ashtagi; Mahesh D Mallapur (Medsci Publications, 2016)
Introduction: Anemia is the most prevalent worldwide nutritional problem, mainly by iron deficiency. Iron deficiency anemia leads to weakness, poor physical growth, and a compromised immune system, decreasing the capacity to fight infections and thereby increasing morbidity and is also found to impair cognitive performance in a child. Objective: To assess the severity of anaemia among urban and rural children of Belagavi Methodology: Government aided schools from Vantamuri PHC and Ramnagar UHC were selected for the study. Probability proportionate to the size sampling technique was used to select sample from each school. Students were selected from each class by simple random sampling. Hemoglobin estimation was done by using Sahli's Acid Hematin method. Results: Prevalence of anaemia among school children in Belagavi was found to be 47.9%. A high prevalence of 57% was seen among girls and 40.5% of the boys were anaemic. Prevalence was more in rural area i.e. 52.7% compared to that of urban i.e. 43%. Mild anaemia was found to be more prevalent in both urban and rural children i.e. 28.7% and 29.7% respectively. Conclusion: The urban and rural areas in our study fall in to communities of severe public health significance (prevalence >40%). There was a higher prevalence of mild anemia as compared to moderate and severe anemia.